2010
DOI: 10.1007/s11664-010-1332-z
|View full text |Cite
|
Sign up to set email alerts
|

On the Placement of Thermoelectric Generators in Automobiles

Abstract: The placement of thermoelectric generators (TEGs) in vehicles is analyzed, taking into account the interaction of the TEG with the internal combustion engine (ICE). Alternative locations of the TEG directly in the ICE, on the exhaust pipe, and on the cooling system are considered. In all three cases there is a conflict between the two thermal machines, which reduces the total efficiency of the thermodynamic (ICE + TEG) system. It is shown that the cause of the conflict is the low efficiency of the TEG (g TEG <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…According to Riffat and Xiaoli (2003), another possible application could be power generation in spacecraft and TEG power plants on Mars. Recovery of excess heat from automobiles to save fuel has been studied (e.g., Korzhuev and Katin 2010;Kumar et al 2013;Tatarinov et al 2012;and Wang et al 2013c). O'Shaughnessy et al (2013) presented results from small-scale electricity generation with a TEG integrated with a cooking stove.…”
Section: Thermoelectric Generator (Teg)mentioning
confidence: 99%
“…According to Riffat and Xiaoli (2003), another possible application could be power generation in spacecraft and TEG power plants on Mars. Recovery of excess heat from automobiles to save fuel has been studied (e.g., Korzhuev and Katin 2010;Kumar et al 2013;Tatarinov et al 2012;and Wang et al 2013c). O'Shaughnessy et al (2013) presented results from small-scale electricity generation with a TEG integrated with a cooking stove.…”
Section: Thermoelectric Generator (Teg)mentioning
confidence: 99%
“…The dimension of the system is large and extra added weight will increase the inertia. Korzhuev [10] considered the IC Engine and TEG as single thermodynamics system and then defined their economic feasibility. Their observation was conflict between power output and back pressure caused by adding TEG.…”
Section: Introductionmentioning
confidence: 99%
“…Hendricks [17] analyzed the potential of TEG systems in vehicle wasted heat recovery, and optimized the TEG and heat exchanger design. Korzhuev et al [18] placed TEGs in different locations of vehicle, such as engine, exhaust pipe and cooling system. Kim et al [19] developed a TEG system with the engine coolant of light-duty vehicles as heat source, and the output power is about 75 W. In their study, the conventional radiators of the existing water cooling system were replaced by the TEG system.…”
Section: Introductionmentioning
confidence: 99%
“…According to the review of previous studies for exhaust heat recovery by TEG, it is found that these studies mainly focused on the steady-state TEG performance [16][17][18][19][20][21]. However, there are few studies for the transient behavior of TEG in vehicle dynamic driving conditions and driving cycles [25].…”
Section: Introductionmentioning
confidence: 99%